Biosensor-Integrated Drug Delivery Systems as New Materials for Biomedical Applications - Cicha, Iwona; Priefer, Ronny; Severino, Patricia; Souto, Eliana B.; Jain, Sona (Biomolecules, 2022)
Biosensor-integrated drug delivery systems are innovative devices in the health area, enabling continuous monitoring and drug administration. The use of smart polymer, bioMEMS, and electrochemical sensors have been extensively studied for these systems, especially for chronic diseases such as diabetes mellitus, cancer and cardiovascular diseases as well as advances in regenerative medicine. Basically, the technology involves sensors designed for the continuous analysis of biological molecules followed by drug release in response to specific signals. The advantages include high sensitivity and fast drug release. In this work, the main advances of biosensor-integrated drug delivery systems as new biomedical materials to improve the patients’ quality of life with chronic diseases are discussed.
CRIS-Team Scopus Importer:2022-10-07
Keywords: biomedical applications; biosensors; chronic treatments; drug delivery systems; smart polymers